Analysis of Malaysian beef industry in Peninsular Malaysia under different importation policies scenarios and rate management systems - Mohamed, Zainal Abidin; Hosseini, Anahita; Kamarulzaman, Nitty Hirawaty (Universiti Putra Malaysia Press, 2013)
In Malaysia, the production of fresh beef is inadequate to meet the people’s demand. The major problem is that the beef sub sector of Malaysia has remained uncommercialized due to low productivity and the private sector has been silent on the beef sub sector development. Malaysia imported 75-80% of her beef requirement from different parts of the world in order to meet the domestic demand. Thus drastic policies need to be formulated to terminate dependency on others while developing beef industry domestically as an import substitution strategy. Thus the objective of this study is to develop a beef production system modeling for policy analysis via a model known as the Vintage approach simulation matrix model (VASIMM). VASIMM has the ability to determine the effect of the importation of the breeding stock policy and calculate the benefit and cost of implementing such policy to the government in the long run. The VASIMM method uses aggregate data to bring the new breeding stock into the model. Among the data feasible include reports that derive the reproduction of existing breeding stocks, determine the culling rate, and derive a theoretical slaughter system based on different rates of calving, replacement, mortality, and slaughter in the past. In addition, the method is able to determine reduction rates for system simulation, simulate final results of female and male breeding stocks, iv) female and male calves, ,rate of slaughter, and production of beef from beef cattle, dairy cattle, and buffalo . The ex-ante simulation analysis was developed by examining different policy variables, and report issues on mortality, slaughter, and calving rate, importation of female breeding stocks, and importation of animal for slaughter, in 9 different Policy Scenarios. Result from these 9 Scenarios indicate that only Scenario 3 is economically applicable in the long run which can fulfill the targeted level of self-sufficiency (40%) by 2020.